Faith, Freedom, and Femininity: Rethinking Misyar Marriage in the Modern Muslim World (Voice of History, 2025)
Misyar marriage represents a form of marital contract sanctioned under particular interpretations of Islamic jurisprudence, wherein one or both spouses voluntarily relinquish specific marital rights and obligations such as shared residence or financial maintenance. Although legally valid in several Sunni majority contexts, this arrangement has provoked extensive theological, ethical, and socio-legal debate across the Muslim world. This study critically explores Misyar marriage through the integrated lenses of Islamic jurisprudence, gender ethics, and socio-cultural analysis. Employing a qualitative research framework, it draws upon scholarly discourse, juridical opinions, and in-depth interview-based insights to investigate the broader implications of Misyar on women’s rights, family integrity, and Islamic moral philosophy. The analysis argues that while Misyar may provide flexibility for certain individuals constrained by economic or social circumstances, it simultaneously operates within patriarchal structures that undermine women’s autonomy and the ethical spirit of Islamic marriage. The paper investigates that a nuanced reevaluation of Islamic marital jurisprudence, one that harmonizes legal permissibility with ethical accountability and evolving social realities, is essential for achieving justice and moral coherence in contemporary Muslim societies.